Pulse plating of platinum on aligned multiwalled carbon nanotubes. (July 2013) - Schneider, M.; Weiser, M.; Dörfler, S.; Althues, H.; Kaskel, S.; Michaelis, A.
Abstract : In the present study, the electrochemical deposition (ECD) of platinum particles on aligned multiwalled carbon nanotube (MWCNT) arrays as novel membrane electrode assembly (MEA) in polymer electrolyte membrane fuel cells was investigated. The ECD was performed using the pulse plating technique and an electrolyte based on potassium tetranitroplatinate(II) salt. The MWCNTs were produced on thin nickel foils by chemical vapour deposition. The MWCNT arrays were electrochemically characterised by cyclic voltammetry in sulphuric acid. The platinum functionalisation of the MWCNT arrays was also investigated by cyclic voltammetry and by scanning electron microscopy. The final preparation of the MEA functionalised MWCNT on Nafion was performed by a hot pressing process.